Towards common principles of flexicurity : more and better jobs through flexibility and security (Office for Official Publications of the European Communities, 2007)
Flexicurity is a combination of fl exibility and security in working arrangements. The concept is a response to the needs European labour markets are facing. On the one hand, the EU has to come to terms with changes in the world economy. Technological developments are becoming ever more rapid. Products and services are developed at an ever quicker pace. If Europe wants to strengthen its economy and create jobs, it has to be in the forefront of these developments. Enterprises have to move towards innovative product and service development. They have to master new skills and production techniques. This is a continuous process, affecting employers and workers alike. Jobs change more quickly than before. The ability to adapt and readiness for change are becoming more and more important. On the other hand, the EU needs to reinforce the European social models, which are committed to social protection, social cohesion and solidarity. Workers need suffi cient security to plan their lives and careers with support to make it through all these changes and stay in employment. They need opportunities to master new skills and help to move from one job to another. They need protection against bad working conditions. They need good social protection in case a new job is not easily at hand or when employment is no longer a realistic option.